Pengaruh Profitabilitas, Solvabilitas, Capital Itensity, dan Growth terhadap Penghindaran Pajak: Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di BEI Tahun 2018-2022 - Luky Habibbatunnajikhah; Dewi Kirowati; Ahmad Kudhori (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study expects to decide the impact of productivity, dissolvability, capital force, and development on charge evasion. The financial statements of energy sector companies listed on the Indonesia Stock Exchange serve as the source of the secondary data used in this study. This study's participants are 78 energy sector issuers listed on the Indonesia Stock Exchange between 2018 and 2022. The technique utilized by this exploration utilizes purposive examining strategy, where the example is 22 organizations that have met the standards. The autonomous factors in this study are benefit, dissolvability, capital power, development, and the reliant variable assessment evasion. The consequences of the review utilized numerous straight relapse examination, utilizing SPSS form 26 with a huge degree of 0.05. According to the findings of this study, solvency of 0.380 and growth of 0.586 have no effect on tax evasion. In the interim, benefit of 0.006 and capital power of 0.000 impact charge evasion.